Asian Perspective of Artificial Intelligence in Hiring: A Systematic Review - Maria Batool; Muhammad Rashid; Zafar Iqbal Khan; Arfan Akbar; Humera Omer Farooq; Imran Zafar Butt (Al-Qanṭara, 2023)
Artificial intelligence (AI) is the ability of technology, either algorithms or computers to carry all those activities that would otherwise need human brain or intelligence. It has the potential to play a pivotal role in an organization's overall strategy due to its ability to synthesize information, perform a sequence of tasks and draw conclusions based on it. The purpose of the present study is to conduct a systematic review on the uses and applications of AI in hiring process by HR professionals from an Asian perspective. The most recent and relevant literature on artificial intelligence in hiring was compiled from research studies published from 2018 to 2023 in the Scopus database. The data was filtered to select English and studies conducted in Asian countries only. The total of 20 qualitative studies were reviewed systematically. The Mixed Methods Appraisal Tool version 2018 was used to assess and ensure quality of the selected studies. To collate and synthesize an overview of AI applications in hiring process, PRISMA methodology has been used. Descriptive analysis shows most of the studies are from India and other Asian countries also contributing to the field. The graph of year-wise publications shows that the use of artificial intelligence in the process of recruitment and hiring is increasing and organizations are paying close attention to the use of AI. Articles from Research Gate, Taylor and Francis, Emerald and Elsevier, Springer, SAGE and Wiley were considered for the current systematic review due to their authenticity and significance. 60% of articles are related to human resource management, with 20% from IT. This demonstrates the collaborative efforts of IT experts with HR professionals to use AI in recruitment. After extensive review of literature, it is concluded that AI applications are particularly useful in effective recruitment strategies, as quality of talent is essential for organizations in competitive environments. The current generation is taking advantage of formal learning opportunities and technology to use AI-based technologies in shifting circumstances. AI-powered systems must be contemporary, secure, safe and with friendly user interface for both recruiters and potential candidates. This study will help organizations decide which technology to use for upgrading their recruitment process based on skills, number of hires, budget, and time. AI also plays a role in improving behavioral and psychometric assessments and recruitment. This area should be studied utilizing sequential exploratory inquiry and deductive methods. This hybrid topic requires a multidisciplinary examination in future.